On the Role of Single Particle Irradiation and Fast Timing for Efficient Online-Control in Particle Therapy - Dauvergne, Denis; Allegrini, Oreste; Caplan, Cairo; Chen, Xiushan; Curtoni, Sébastien; Etxebeste, Ane; Gallin-Martel, Marie-Laure; Jacquet, Maxime; Létang, Jean Michel; Livingstone, Jayde; Marcatili, Sara; Morel, Christian; et al. (Frontiers in Physics, 2020)
Within the frame of the CLaRyS collaboration, we discuss the assets of using a reduced-intensity in vivo treatment control phase during one or a few beam spots at the beginning of a particle therapy session. By doing so we can improve considerably the conditions for secondary radiation detection and particle radiography. This also makes Time-of-Flight (ToF) resolutions of 100 ps rms feasible for both the transmitted particles and secondary radiations, by means of a single-projectile counting mode using a beam-tagging monitor with time and position registration. This opens up new perspectives for prompt-gamma timing and Compton imaging for range verification. ToF-based proton computed tomography (CT) and ToF-assisted secondary proton vertex imaging in carbon therapy are also discussed, although for the latter, no evidence of any benefit at small observation angles is anticipated. The reduction of the beam intensity during one or a few spots on the various accelerators for particle therapy should not significantly reduce the patient workflow.